The Neutralizing Antibody Response Elicited by Tembusu Virus Is Affected Dramatically by a Single Mutation in the Stem Region of the Envelope Protein - Lv, Junfeng; Liu, Xiaoxiao; Cui, Shulin; Yang, Lixin; Qu, Shenghua; Meng, Runze; Yang, Baolin; Feng, Chonglun; Wang, Xiaoyan; Zhang, Dabing (Frontiers in Microbiology, 2020)
Tembusu virus (TMUV) is a mosquito-borne flavivirus that most commonly affects adult breeder and layer ducks. However, a TMUV-caused neurological disease has also been found in ducklings below 7 weeks of age, highlighting the need to develop a safe vaccine for young ducklings. In this study, a plaque-purified PS TMUV strain was attenuated by serial passage in BHK-21 cells. Using one-day-old Pekin ducklings as a model, the virus was confirmed to be attenuated sufficiently after 180 passages, whereas the neutralizing antibody response elicited by the 180th passage virus (PS180) was substantially impaired compared with PS. The findings suggest that sufficient attenuation results in loss of immunogenicity in the development of the live-attenuated TMUV vaccine. Comparative sequence analysis revealed that PS180 acquired one mutation (V41M) in prM and four mutations (T70A, Y176H, K313R, and F408L) in the envelop (E) protein. To identify the amino acid substitution(s) associated with loss of immunogenicity of PS180, we rescued parental viruses, rPS and rPS180, and produced mutant viruses, rPS180-M41V, rPS180-A70T, rPS180-H176Y, rPS180-R313K, rPS180-L408F, and rPS180-M5, which contained residue 41V in prM, residues 70T, 176Y, 313K, and 408F in E, and combination of the five residues, respectively, of PS in the backbone of the rPS180 genome. The neutralizing antibody response elicited by rPS180-L408F and rPS180-M5 was significantly higher than those by other mutant viruses and comparable to that by rPS. Furthermore, we produced mutant virus rPS-F408L, which contained residue 408L of PS180 in the backbone of the rPS genome. The F408L mutation conferred significantly decreased neutralizing antibody response to rPS-F408L, which was comparable to that elicited by rPS180. Based on homologous modelling, residue 408 was predicted to be located within the first helical domain of the stem region of the E protein (EH1). Together, these data demonstrate that a single mutation within the EH1 region exerts a dramatical impact on the TMUV neutralizing antibody response. The present work may enhance our understanding of molecular basis of the TMUV neutralizing antibody response, and provides an important step for the development of a safe and efficient live-attenuated TMUV vaccine.